MODE CHOICE ANALYSIS OF JEMBER-SURABAYA LAND TRANSPORTATION USING STATED PREFERENCE METHOD - Asa Dina Safitri; Paksitya Purnama Putra; Akhmad Hasanuddin (Jurnal Rekayasa Sipil dan Lingkungan, 2020)
The launched of the new Probolinggo-Pasuruan toll road affected the Express Bus route from Jember to Surabaya. Taken from a third party application, the travel time for the Jember-Surabaya Express Bus route changes faster. The acceleration of travel time is 1 hour, from 4 hours 30 minutes to 3 hours 30 minutes. The initial hypothesis of this change is a change in public interest as users of the mode of transportation from the Train to the Express Bus. The Stated Preference method is used to determine people's preferences. Based on the analysis results, there are two utility model results obtained from the travel cost difference attribute and the travel time difference attribute with an R² value of 0.995. Based on the results of the sensitivity analysis, the greater the difference between the cost of travel and the difference in travel time, the probability of train passengers to move using the Express Bus will continue to increase. Peresmian tol baru Probolinggo-Pasuruan mempengaruhi rute Bus Patas dari Jember ke Surabaya. Diambil dari aplikasi pihak ketiga, waktu tempuh rute Bus Patas Jember-Surabaya berubah lebih cepat. Percepatan waktu tempuh adalah sebesar 1 jam, dari 4 jam 30 menit menjadi 3 jam 30 menit. Hipotesis awal dari adanya perubahan tersebut adalah akan adanya perubahan minat masyarakat sebagai pengguna moda transportasi dari Kereta Api ke Bus Patas. Metode Stated Preference digunakan untuk menentukan preferensi orang. Berdasarkan hasil analisis terdapat dua hasil model utilitas yang diperoleh dari atribut perbedaan biaya perjalanan dan atribut perbedaan waktu tempuh dengan nilai R² sebesar 0,995. Berdasarkan hasil analisis sensitivitas, semakin besar selisih biaya perjalanan dengan selisih waktu tempuh maka probabilitas penumpang Kereta Api untuk berpindah menggunakan Bus Patas akan terus meningkat.